In silico analyses of rare CFTR variants from The Turkish National Cystic Fibrosis Patient Registry to predict their functional effects - Kara, A. S.; Yavuz, B. Capraz; Sen, V.; Sen, H. Selimoglu; Celebi, O.; Oztosun, B.; Erden, D. Dayangac (Wiley, 2025)
[Abstract Not Available]